Sistem Informasi Manajemen Pendataan Sandang dan Penjualan Online pada Toko DRESSCODE berbasis Web menggunakan metode Waterfall SDLC - Faldo Sabillah Shidqi; Edy Santoso; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Sistem Informasi Manajemen Pendataan Sandang Dan Penjualan Online is a system that created to aid the store owner and manager in managing goods so there wont be any mistakes managing and listing products. And costumer could access the store catalog without have to visit the store, and the store owner could see the trend based on the number products visited on the website. The system could also list the products that are running out of stock so the store manager could re-stock the items. And then theres a feature that shows income of the store. The software development process starts from analyzing the requirements and object oriented testing. There are 21 functional requirements based on the analyzing phase. The implementation phase was carried out using Laravel. Unit testing produces 100% valid data from 3 tested function, while the validation test produces 100% valid data from 21 tested function. Compatibility Tests were done using 3 different browsers : Google Chrome, Mozilla Firefox, and Microsoft Edge.